Australian Dental Practitioners’ Experience and Confidence in Providing Oral Health Care for People With Cerebral Palsy and Other Disabilities - Lansdown, Karen; Zagreanu, Claudia; Bulkeley, Kim; McGrath, Margaret; Irving, Michelle; Smithers-Sheedy, Hayley (ANZJDOHT, 2025)
Objective: To investigate dental practitioners’ experience and confidence in providing oral health care for people with cerebral palsy (CP) and other disabilities in Australia. Methods: A cross-sectional online survey exploring dental care for people with CP and other disabilities was distributed to registered dental practitioners. Snowball sampling was used to recruit participants via professional associations and social media. Data was collected between December 2023 and August 2024. Descriptive statistics were used to summarize the findings. Results: Fifty-six surveys were completed by oral health therapists (48%), dentists (25%), dental hygienists (13%), dental therapists (9%), and specialists in special needs dentistry (5%). Most were female (88%) and based in major cities (62%). Clinical experience varied from <10 years (30%), 11 to 20 years (29%) and >20 years (39%). More than half the dental practitioners (57%) had received disability-related training. For most practitioners (64%) people with disabilities made up less than 10% of their patient population. Participants reported moderate confidence and experience working with people with disabilities more generally but were less confident and experienced providing services for people with CP. Commonly reported challenges in working with people with CP and people with other disabilities included perceived difficulties with cooperation (52%), accessibility (57%) and behavioural concerns (70%). Most but not all dental practitioners were aware of appropriate referral pathways (80%). Most dental practitioners were interested in further education, particularly CP-specific training, (91%), online modules (87%) and formal accreditation (59%). Conclusion: Improving oral health for people with CP and other disabilities requires a trained and experienced workforce and accessible services. Building clinical skills, expanding education and improving accessibility are key to supportive effective care. Investment in post graduate education in disability-inclusive practice for oral health practitioners, clearer referral pathways and inclusive infrastructure may build a more confident and responsive dental workforce.
Keywords: 320312 Special needs dentistry; 39 Education; 3203 Dentistry; Cerebral palsy; disability; dental practitioner; experience; confidence; attitudes